From mat weavers to box-makers: agency, development, and the production of heritage in Sri Lanka. Issue 6 (18th August 2022) - Greru, Chamithri
ABSTRACT: The mediation of development agencies is a growing concern for the Global South. Further research is needed to explore the manner in which authorised notions of development cascade down to the more discrete levels of society and alter understandings of heritage. This paper presents everyday narratives of craftswomen working in an export production village, discussing how development brings significant social, cultural, material, and economic changes. Highlighting the paradox of development – that it can intensify the very marginalisation it seeks to overcome – the paper suggests the need for careful integration of heritage within development activities.